MATERNAL SERUM ENDOCAN AS A POTENTIAL PREECLAMPSIA MARKER - Peby Maulina Lestari (Majalah Kedokteran Sriwijaya, 2021)
Preeclampsia remains the leading cause of maternal and neonatal morbidity and mortality worldwide. The imbalance of interactions between the placenta, immunity and the maternal cardiovascular system also plays a role in preeclampsia. Early onset preeclampsia (POD) and advanced onset preeclampsia (POL) are thought to have different pathomechanisms, causing different clinical symptoms. One theory of preeclampsia is the occurrence of endothelial dysfunction. Endocan as a specific endothelial protein is also thought to have an effect. Various studies on the role of Endocan in cardiovascular disease have also been carried out, while its role in preeclampsia that occurs in pregnant women is still very minimal. This study aims to determine the role of Endocan as a specific endothelial protein in preeclampsia. The study design was cross-sectional. A total of 72 subjects (24 subjects each in the POD, POL and normotensive pregnancy groups) were selected by consecutive sampling. Enzym Linked Immunoabsorbant Assay (ELISA) was performed to assess the Endocan concentration. In general, there is no significant difference in the characteristics of research subjects. Endocan concentrations were found to be higher in the POD group, while in the POL and normotensive pregnancy groups there was no significant difference. Endocan can be considered as a potential marker of preeclampsia, especially early onset.